(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The continental passive margins, as the Argentine Continental Passive Volcanic Margin (MCAPV) (Franke et al., 2007; Schnabel et al., 2008; Becker et al., 2012), preserve in their sedimentary record eustatic changes and variations in the dynamics of the ocean currents, from global changes, as opening and closure of ocean gateways, to local variations, as changes in depth in the boundary of different water masses. The Patagonian Continental Margin (MCP) is the portion of the MCAPV located south to the Colorado Fracture Zone (Fig. 1 a, b). The major features shaping the surface of the continental slope in the MCP are four contouritic terraces (Fig. 1b), from west to east: Nágera Terrace (TN), Perito Moreno Terrace (TPM), Piedra Buena Terrace and Valentín Feilberg Terrace. The genesis and evolution of the four terraces is linked to the activity of antartic sourced bottom currents. Previous works have described the seismos- tratigraphy and the oceanographic controls in the structural building of the two easternmost terraces, (e.i., Piedra Buena and Valentín Feilberg terraces). On the contrast, very little is known on the evolution of the Nágera and Perito Moreno terraces. This work aims to describe the Cenozoic strati- graphy of the TN ( 600 a 1000 m) and TPM ( 1000 a 1500 m), in relation to the major climatic and oceanographic changes occurred in the South Atlantic Ocean during this time. The study is based on the interpretation of two monochannel seismic lines acquired in 2014 on board of the Canadian vessel Coriolis II, and one multichannel seismic line provided from Secretaría de Energía de la Nación Argentina. Through the interpretation of the seismic lines (Figs. 2-4), following the seismostratigraphic method (Mitchum et al., 1977), four mayor unconformities were recognized (Table 1). These unconformities are interpreted as sequence boundaries. After correlate this unconformities with: previous works in the MCA (data published of Tayra well by Continanzia et al., 2011; and cores published by Ewing & Lonardi, 1971) and main oceanographic-climatic changes, five seismic units (U0, U1, U2, U3 and U4; see table1) were defined for this part of the margin. Finally, by the interpretation of these units, four stages of evolution for the TN and TPM could be defined (Fig. 5): 1) Paleocene - Eoceno, is characterized by thermal subsidence, as well as hemipelagic and gravitational sedimentation with negligible activity of deep ocean currents. 2) Eocene - Oligocene to mid Miocene, is characterized by the presence of a shallow marine environment with clinoforms in the outer shelf to middle slope, and it is interpreted as a deltaic progradation in a shallow sea environment. 3) Middle Miocene to Pliocene, is characterized by the first evidence of current activity in the area. It finishes with a strong erosive surface, and formation of the Nágera and Perito Moreno terraces. 4) Pliocene to Holocene is characterized by high ocean currents activity in the upper and middle slope, strong interaction between ocean currents and the seafloor, and development of contouritic deposits.